Career Accreditation Agencies at the University of Costa Rica: their self-Assessment models (Revista Electrónica Calidad en la Educación Superior, 2022)
The self-evaluation processes with a view to accreditation refer to the accreditation of curricular proposals, that is, university careers. In the framework of the research "Relating Pedagogy, Curriculum and Didactics: the case of the UCR majors reaccredited by the SINAES", the self-evaluation model proposed by each agency that has accredited majors at the University of Costa Rica is analyzed, they are the National System of Accreditation of Higher Education (SINAES), the Canadian Agency for Accreditation of Engineering and the Central American Agency for Accreditation of Engineering, Architecture and Design. In the three self-assessment models, the vision of quality prevails as the fulfillment of criteria demonstrated by various evidences.
Keywords: Accreditation; Higher Education; Accreditation Agencies